1998
DOI: 10.1142/s0218625x98001353
|View full text |Cite
|
Sign up to set email alerts
|

Na and Cl2 Interaction on it and 2H–TaSe2(0001) Surfaces

Abstract: In this paper we study the interaction of Cl2 and Na on 1T-TaSe2 and 2H-TaSe2(0001) surfaces in the temperature range of 100-300 K. The experiments are performed in UHV with the use of LEED and SXPS by synchrotron radiation measurements. Deposition of Na on Cl2-covered 1T-TaSe2 at 100 K forms initially a Na-Cl − 2 , which with increasing temperature to 300 K leads to NaCl formation. Adsorption of Cl2 on Na-intercalated 1T and 2H-TaSe2 surfaces at 100 K forms Cl2 multilayers. The first Cl2 layer, in contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Deposition of Na at 100 K after exposure and subsequent warming to 300 K resulted in NaCl formation without intercalation. In a similar study, Papageorgopoulos et al [56] found that the induced de-intercalation of Na was much faster on 2H-than on In a TEM study by Remškar et al [76] it was observed that prolonged exposure of Cs intercalated to air resulted in de-intercalation and growth of on the surface, predominantly where the surface was cracked. …”
Section: Crystallographic Structurementioning
confidence: 94%
“…Deposition of Na at 100 K after exposure and subsequent warming to 300 K resulted in NaCl formation without intercalation. In a similar study, Papageorgopoulos et al [56] found that the induced de-intercalation of Na was much faster on 2H-than on In a TEM study by Remškar et al [76] it was observed that prolonged exposure of Cs intercalated to air resulted in de-intercalation and growth of on the surface, predominantly where the surface was cracked. …”
Section: Crystallographic Structurementioning
confidence: 94%